Field Evaluation of Four Insecticides for the Control of the Mango Leaf-cutting Weevil, Deporaus marginatus Pasco - Soh, P. G.; Khoo, Khay Chong (1983)
In an insecticidal trial for the control of the leaf-cutting weevil of mango, Deporaus marginatus Pasc., deltamethrin was the most effective insecticide followed by etrimfos, acephate and dicrotophos in that order. A persistency study of deltamethrin in the field showed that the insecticide was effective for up to two weeks.